Minute ventilation in cardiorespiratory exercise and its relationship with ventricular ejection fraction - Alirio Bastidas-Goyes; Eduardo Tuta-Quintero; Juan D. Botero; Daniel Botero-Rosas; Daniel Prieto; Daniela Rubio; Cristian Lopez; Gustavo A. Hincapie; Barbarita Mantilla; Abraham Brito; Tatiana Vargas; Stefania Forero; et al. (Revista Cubana de Medicina Militar)
Introduction: Cardiorespiratory exercise testing is a non-invasive alternative in the assessment of subjects with heart failure. Objective: To evaluate the validity of ventilatory equivalents for carbon dioxide (VE/VCO2) as a predictor of left ventricular ejection fraction (LVEF) compared to peak oxygen consumption. Methods: Cross-sectional analytical study in patients undergoing cardiopulmonary exercise testing and transthoracic echocardiography. The study was divided into a group with reduced LVEF < 40 % and preserved = 40 %. Bivariate analysis comparing qualitative variables with the chi-square test and quantitative variables with Student's t-test was performed. A Receiver Operating Characteristic (ROC) curve was constructed to evaluate the discriminatory capacity between ventilatory equivalent for carbon dioxide and peak oxygen pulse. Results: The final analysis included 138 patients. In patients with reduced LVEF, peak oxygen consumption averaged 1.6 L/min (SD ± 0.68) compared to 1.7 L/min (SD ± 0.66) in the control group (p= 0.513). VE/VCO2 during ventilatory threshold and peak exercise averaged 38.4 (SD ± 7.38) and 44.6 (SD ± 8.24), respectively. The discriminatory performance of VE/VCO2 versus peak oxygen consumption was 0.737 (95 % CI: 0.596-0.878; p= 0.008) in patients with reduced LVEF. Conclusions: VE/VCO2 is a reliable predictor of normal or reduced LVEF and performs well compared to peak oxygen consumption.